Studi Pemikiran Abdul Rahman Masmud Pendekatan Humanisme Religius - Imroatul Janah; Nayla Khoirunnisa; Fitri Arilia (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article discusses Abdul Rahman Masmud’s thoughts on the religious humanism approach, a concept that integrates human values with the principles of religiosity. This approach emphasizes the balance between universal moral values and religious values, aiming to create harmony in social and spiritual life. This study uses a qualitative method through a literature study of Abdul Rahman Masmud’s works. The results show that Masmud’s thoughts make a significant contribution to the development of religious-based social ethics that are relevant to multicultural and modern contexts.